2014
DOI: 10.1590/s1413-65382014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Altas habilidades/superdotação no contexto escolar: percepções de professores e prática docente

Abstract: RESUMO: esta pesquisa objetivou explorar as concepções de professores do Ensino Fundamental da rede pública de Vitória-ES sobre altas habilidades/superdotação (AH/SD), verificando as relações entre essas concepções e a prática docente dos participantes, avaliando também a concepção dos mesmos quanto à adequação de sua formação profissional para lidar com pessoas com AH/ SD e investigando as principais estratégias de ensino e aprendizagem utilizadas pelos mesmos. Para a coleta de dados utilizou-se um roteiro de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
1
9
0
9
Order By: Relevance
“…The analysis in this study exhibit what teachers' understanding and perception about the giftedness in the preschool. Some authors described in their research what teacher's represent the giftedness is a special need and a specific characteristic on the development and the learning in different school levels [3,4,7,8].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis in this study exhibit what teachers' understanding and perception about the giftedness in the preschool. Some authors described in their research what teacher's represent the giftedness is a special need and a specific characteristic on the development and the learning in different school levels [3,4,7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, research has also shown that the perception of giftedness includes definitions, conceptions, characteristics, theoretical frames of reference, and many other features related to giftedness and the gifted. Therefore, when assessing teachers' perceptions of giftedness, it is necessary to take into account what teachers understand about giftedness and who is for him/her a gifted student [4,13]. In this way, the teacher's perception of giftedness is essential for the recognition of his/her gifted students.…”
Section: Giftedness In Schoolmentioning
confidence: 99%
See 2 more Smart Citations
“…Vale ressaltar que a incidência dessas características é variada de acordo com a singularidade do sujeito, sendo que algumas delas são muito notórias e outras pouco aparentes em um mesmo indivíduo, justamente pelo caráter multidimensional das altas habilidades/ superdotação. Outro aspecto importante a ser destacado é os mitos e verdades que a temá-tica das AH/SD possui, pois esses aspectos dificultam a identificação e a intervenção não só com esse público, mas também com a família, escola e sociedade (BAHIENSE; ROSSETTI, 2014).…”
unclassified